Corticosteroids and superinfections in COVID-19 patients on invasive mechanical ventilation. Issue 1 (July 2022) - Søvik, Signe; Barrat-Due, Andreas; Kåsine, Trine; Olasveengen, Theresa; Strand, Marianne Wigernes; Tveita, Anders Aune; Berdal, Jan Erik; Lehre, Martin Andreas; Lorentsen, Torleif; Heggelund, Lars; Stenstad, Tore; Ringstad, Jetmund; et al.
Highlights: In COVID-19 ARDS superinfections were strongly associated with the use of dexamethasone. Invasive fungal infections were found exclusively in dexamethasone treated patients. Unadjusted survival rate was decreases in patients treated with dexamethasone. Abstract: Objectives: To determine the incidence and characteristics of superinfections in mechanically ventilated COVID-19 patients, and the impact of dexamethasone as standard therapy. Methods: This multicentre, observational, retrospective study included patients ≥ 18 years admitted from March 1 st 2020 to January 31 st 2021 with COVID-19 infection who received mechanical ventilation. Patient characteristics, clinical characteristics, therapy and survival were examined. Results: 155/156 patients (115 men, mean age 62 years, range 26-84 years) were included. 67 patients (43%) had 90 superinfections, pneumonia dominated (78%). Superinfections were associated with receiving dexamethasone (66% vs 32%, p<0.0001), autoimmune disease (18% vs 5.7%, p<0.016) and with longer ICU stays (26 vs 17 days, p<0, 001). Invasive fungal infections were reported exclusively in dexamethasone-treated patients [8/67 (12%) vs 0/88 (0%), p<0.0001]. Unadjusted 90-day survival did not differ between patients with or without superinfections (64% vs 73%, p=0.25), but was lower in patients receiving dexamethasone versus not (58% vs 78%, p=0.007). In multiple regression analysis, superinfection was associated with dexamethasone use [OR 3.7 (1.80–7.61), p<0.001], pre-existing autoimmune disease [OR 3.82 (1.13–12.9), p=0.031] and length of ICU stay [OR 1.05 p<0.001]. Conclusions: In critically ill COVID-19 patients, dexamethasone as standard of care was strongly and independently associated with superinfections.